Reliability of ultrasound in combination with surface electromyogram for evaluating the activity of abdominal muscles in individuals with and without low back pain - Yang, Kyung-Hye (Korean Society of Exercise Rehabilitation, 2014)
This study investigated the reliability of ultrasound in combination with surface electromyogram (EMG) for evaluating the activity of the abdominal muscles in individuals with and without low back pain during the abdominal drawing-in maneuver (ADIM). The study recruited ten individuals with or without low back pain, respectively. While the participants were performing the ADIM, the activities of the transversus abdominis (TrA) and the internal oblique (IO) were measured using ultra-sound, while the activities of the external oblique (EO) and the rectus abdominis (RA) were measured using surface EMG. Intra-class correlation coefficients (ICC) were used to verify the inter-rater reliability of ultrasound in combination with surface EMG at rest and during the ADIM, and Bland-Altman plots were used to verify intra-rater reliability. The inter-rater reliability for the two groups at rest and during the ADIM was excellent (ICC(2,1) = 0.77–0.95). In the Bland-Altman plots, the mean differences and 95% limits of agreement in the abdominal muscles of the two groups at rest were −0.03∼0.03 mm (−0.66 to 0.60 mm) and −0.12∼ −0.05 (−0.58 to 0.48% MVIC), respectively. The mean differences and 95% limits of agreement in the abdominal muscles of the two groups during the ADIM were −0.04∼0.02 mm (−0.73 to 0.65 mm) and −0.19∼0.05% MVIC (−1.24 to 1.34% MVIC), respectively. The ultrasound in combination with surface EMG showed excellent inter-rater and intra-rater reliability at rest and during the ADIM.